Macroalgae Abundance And Cover As Ecological Indicators Of Coral Reef Management In The Waters Of Katapang Village, West Seram Regency, Maluku Province - Masudin Sangaji (International Journal of Science and Environment (IJSE), 2022)
Macroalgae are the main competitors for coral reefs in fighting for aquatic ecological space in coral reef ecosystems. The purpose of this research; Knowing the condition of the aquatic environment, the abundance and cover of macroalgae, and the potential of macroalgae for indicators of coral reef management in the coastal waters of Katapang Village. Data on the physical condition of the waters were measured in situ while macroalgae data for each research station were obtained using the LIT (Line Intercept Transect Method). Macroalgae taxa were identified using an identification guide book from FAO (1998). The distribution of each type of macroalgae was mapped spatially based on the distribution conditions of the macroalgae at each study station. The results showed that the condition of the waters of the coral reef ecosystem in Katapang Village was supportive for the growth of macroalgae. The macroalgae found came from 3 orders, 4 families, 5 genera and 8 species. The results also indicate that the abundance and cover of macroalgae determines the shift in dominance in reef ecosystems so that these two factors can be used as indicators of coral reef management.